Faktor Penyebab Terjadinya Kekerasan Dalam Rumah Tangga Dan Upaya Penanggulangannya - Elly Kurniawati (Jatiswara, 2011)
In practice pukum enforcement in Indonesia, the rules of law which are used in penangulangan domestic violence is not just limited to the provisions in the Book of Criminal Law (Penal Code) and Act No.. 23 Year 2002 on Child Protection. As for the articles about crime in the Penal Code which can be used against perpetrators of domestic violence are the provisions that define the special requirements to be the occurrence of criminal acts such as the relationship of father and son or mother and child, as well as the articles that are not determine the presence of these special requirements. Some of the acts that included the scope of domestic violence and has been formulated as a criminal act in Article 304-309 of the Criminal Code is that it formulates a crime against children, Article 356 Paragraph 1, which regulates criminal acts against women as a wife who is only limited to physical violence. Article 285-296 of the Criminal Code governing rape and lewd acts, not fully accommodate other forms of sexual violence and other forms of outside approval. The violence causes violence in the household is the economic factor, namely the demands of subsistence resulting in frequent occurrence of violence, excessive jealousy of the wife or husband, excessive emotions or the hardness of the husband to his wife, a view which assumes that men males higher degree than women. Besides the lack of legal knowledge as well be the cause of domestic violence as for prevention efforts undertaken is an effort perfentif and prevention efforts are refresif namely prevention efforts undertaken after the occurrence of criminal domestic violence.